RT-QuIC: a highly promising diagnostic method for neurodegenerative diseases—advantages and limitations - D. Koníčková; D. Koníčková; D. Hraboš; D. Hraboš; D. Hraboš; D. Hraboš; D. Hraboš; K. Menšíková; K. Menšíková; K. Menšíková; L. Tučková; L. Tučková; et al. (Frontiers in Neurology)
Although it has been more than 200 years since Parkinson’s disease was described, we have not established biomarkers for its definitive diagnosis yet. Moreover, there is a similar case for the entire group of α-synucleinopathies, which are all characterized by the pathological accumulation of aggregated α-synuclein (α-Syn) in the brain and other tissues. In different biological materials (blood, cerebrospinal fluid, saliva, or skin), α-Syn exists in various conformations and various aggregated states depending on the surrounding environment. Lewy bodies have been considered a pathognomonic feature of Parkinson’s disease for over 100 years, and α-Syn has been known to be a key component of Lewy bodies for over 25 years, making it possible to confirm the diagnosis by post-mortem examination of brain tissue. To overcome these limitations, novel analytical seed amplification assays (SAAs) were introduced, and they quickly became one of the most effective diagnostic tools for antemortem detection of α-synucleinopathies. As they require minimal sample amounts to provide consistent, rapid, and reliable results, SAAs are ideally suited for biomarker determination. This review examines SAA analytical and detection methods, their advantages and strengths, as well as their limitations and shortcomings that need to be addressed to establish a reliable and reproducible protocol. This could serve as a diagnostic methodology worldwide to determine the presence of pathological α-Syn protein at early stages and help develop effective disease-modifying treatment.